Negative electrode for lithium metal battery, lithium metal battery comprising same, and method for manufacturing negative electrode for lithium metal battery
By applying a protective layer composed of porous nanostructured particles and polar inorganic particles on the negative electrode of the lithium metal battery, the problems of lithium dendrites and electrolyte consumption are solved, and the cycle characteristics and life of the lithium metal battery are significantly improved.
Patent Information
- Application Number
- CN202380067134.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-19
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-15
AI Technical Summary
The life characteristics of existing lithium metal batteries are deteriorated, mainly due to the formation of lithium dendrites and the consumption of electrolytes.
A negative electrode with a new structure is adopted, including a negative electrode current collector and a protective layer, which consists of porous nanostructured particles and polar inorganic particles to inhibit the formation of lithium dendrites and the consumption of electrolytes.
By using the negative electrode with a new protective layer structure, the cycle characteristics of the lithium metal battery are significantly improved and the battery life is extended.
Smart Images

Figure CN119836694A_ABST
Abstract
Description
Technical Field
[0001] One or more embodiments relate to a negative electrode for a lithium metal battery, a lithium metal battery including the same, and a method of preparing the negative electrode for a lithium metal battery. Background Art
[0002] Currently commercially available lithium batteries mainly use carbon-based negative electrode active materials such as graphite. The volume of carbon-based negative electrode active materials does not change during charge / discharge, which ensures the high stability of lithium batteries. Graphite has a low theoretical capacity of about 372 mAh / g.
[0003] Lithium metal may be used as a negative electrode active material. Lithium metal has a very high theoretical capacity of about 3,860 mAh / g. Due to a side reaction between lithium metal and an electrolyte during charge / discharge, dendrites are formed on the surface of lithium metal and grow to cause a short circuit between the positive electrode and the negative electrode. As a result, the life characteristics of a lithium metal battery including lithium metal are deteriorated.
[0004] There is a need for a method of improving the lifespan characteristics of a lithium metal battery including lithium metal. Summary of the invention
[0005] Technical issues One or more embodiments include a negative electrode for a lithium metal battery having a novel structure.
[0006] One or more embodiments include a lithium metal battery including a negative electrode having a novel structure.
[0007] One or more embodiments include a method of preparing a negative electrode for a lithium metal battery having a new structure.
[0008] Technical Solution According to an embodiment, there is provided a negative electrode for a lithium metal battery, the negative electrode comprising: a negative electrode current collector; and A protective layer is provided on the negative electrode current collector, The protective layer includes a first protective layer and a second protective layer disposed between the first protective layer and the negative electrode current collector. The first protective layer includes porous nanostructured particles, The second protective layer includes polar inorganic particles.
[0009] According to another embodiment, there is provided a lithium metal battery, the lithium metal battery comprising: a positive electrode; the negative electrode described above; and The electrolyte is disposed between the positive electrode and the negative electrode.
[0010] According to yet another embodiment, there is provided a method for preparing a negative electrode for a lithium metal battery, the method comprising: providing a negative electrode current collector; disposing a second protective layer on the negative electrode current collector; and providing a first protective layer on the second protective layer, Wherein, the first protective layer comprises porous nanostructured particles, and The second protective layer includes polar inorganic particles.
[0011] Beneficial Effects According to one aspect, by adopting a negative electrode having a novel protective layer structure, a lithium metal battery having improved cycle characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is a cross-sectional view of a negative electrode according to an embodiment.
[0013] Figure 2 is a cross-sectional view of a negative electrode according to another embodiment.
[0014] Figure 3 is a cross-sectional view of a negative electrode according to another embodiment.
[0015] Figure 4 is a cross-sectional view of a negative electrode according to another embodiment.
[0016] Figure 5 is a schematic diagram of a lithium battery according to an embodiment.
[0017] Figure 6 is a schematic diagram of a lithium battery according to an embodiment.
[0018] Figure 7 is a schematic diagram of a lithium battery according to an embodiment.
[0019] Figure 8 is a cross-sectional view of a lithium battery including a solid electrolyte layer according to another embodiment.
[0020] Fig. 9 is a cross-sectional view of a lithium battery including a solid electrolyte layer according to another embodiment.
[0021] Fig.10 is a scanning electron microscope image of a cross section of the negative electrode prepared in Example 1.
[0022] Fig.11 is a graph showing life characteristics of lithium metal batteries manufactured in Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION
[0023] Reference will now be made in detail to embodiments, examples of which are shown in the accompanying drawings, wherein the same reference numerals always refer to the same elements. In this regard, the embodiments provided may have different forms and should not be construed as being limited to the descriptions set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to explain the various aspects of this description. As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items. Statements such as "at least one (kind / person) of ... " modify the entire column of elements when following a column of elements, without modifying the individual elements in the column.
[0024] During the charge / discharge process of a lithium metal battery using lithium metal as a negative electrode active material, a lithium metal-containing layer may precipitate and dissolve between the negative electrode current collector and the electrolyte layer. As the charge / discharge of the lithium metal battery is repeated, the lithium metal-containing layer may include impurities remaining in the electrode, decomposition products of the electrolyte, and the like. Therefore, since the lithium metal-containing layer includes such impurities, the surface of the lithium metal-containing layer may become rough and hard. Lithium dendrites precipitate on the lithium metal-containing layer having such a rough surface. Such lithium dendrites may continue to grow during the charge / discharge process and may cause a short circuit between the positive electrode and the negative electrode. In addition, as the charge / discharge of the lithium metal battery is repeated, the electrolyte may be continuously consumed due to side reactions, and thus the cycle characteristics of the lithium metal battery may deteriorate sharply.
[0025] Since the negative electrode for a lithium metal battery according to one aspect has a new protective layer structure, the formation of lithium dendrites in the negative electrode active material layer can be suppressed, and the consumption of the electrolyte can be suppressed, thereby improving the cycle characteristics of the lithium metal battery using such a negative electrode.
[0026] Hereinafter, since the inventive concept allows various changes and numerous embodiments, specific embodiments will be shown in the drawings and described in detail in the written description. However, this is not intended to limit the inventive concept to a specific mode of practice, and it will be understood that all changes, equivalents and substitutes that do not depart from the spirit and technical scope are included in the inventive concept.
[0027] The terms used herein are only used to describe specific embodiments and are not intended to limit the inventive concept. Unless the context has a significantly different meaning, the expression used in the singular includes the expression of the plural. As used herein, it will be understood that terms such as "include", "have" and "include" are intended to indicate the presence of features, quantities, steps, actions, components, parts, ingredients, materials or combinations thereof disclosed in the specification, and are not intended to exclude the possibility that one or more other features, quantities, steps, actions, components, parts, ingredients, materials or combinations thereof may exist or may be added. The symbol " / " used herein can be interpreted as "and" or "or" according to the context.
[0028] In the accompanying drawings, the thickness of layers and regions is exaggerated or reduced for clarity. Throughout the specification, the same reference numerals in the drawings represent the same elements. Throughout the specification, it will be understood that when a component such as a layer, a film, a region or a plate is referred to as "on" another component, the component may be directly on the other component or there may be an intermediate component on the other component. Throughout the specification, although terms such as "first", "second", etc. may be used to describe various components, such components should not be limited to the above terms. The above terms are only used to distinguish one component from another. Components having substantially the same functional configuration in this specification and the drawings are represented by the same reference numerals, and their redundant descriptions will be omitted.
[0029] As used herein, the "size" of a particle refers to, for example, the "particle size" of the particle. The term "particle size" refers to the average diameter when the particle is spherical, and refers to the average major axis length when the particle is non-spherical. The particle size can be measured using a particle size analyzer (PSA). The "particle size" is, for example, the average particle size. The "average particle size" refers to, for example, the median particle size (D50). The median particle size (D50) is the particle size corresponding to 50% cumulative volume when the particle size distribution measured by the laser diffraction method is calculated from particles with a smaller particle size.
[0030] The term "metal" as used herein includes all metals and metalloids, such as silicon and germanium, in either the elemental or ionic state.
[0031] As used herein, the term "alloy" refers to a mixture of two or more metals.
[0032] As used herein, the term "electrode active material" refers to an electrode material that can undergo lithiation and delithiation.
[0033] As used herein, the term "negative electrode active material" refers to a negative electrode material that can undergo lithiation and delithiation.
[0034] As used herein, the term "lithiation" and variations thereof refer to the process of adding lithium to a positive electrode active material or a negative electrode active material.
[0035] As used herein, the term "delithiation" and variations thereof refer to the process of removing lithium from a positive electrode active material or a negative electrode active material.
[0036] As used herein, the term "charging" and variations thereof refer to the process of providing electrochemical energy to a battery.
[0037] As used herein, the term "discharge" and variations thereof refer to the process of removing electrochemical energy from a battery.
[0038] As used herein, the terms "positive electrode" and "cathode" refer to the electrode that undergoes electrochemical reduction and lithiation during discharge.
[0039] As used herein, the terms "negative electrode" and "anode" refer to the electrode that undergoes electrochemical oxidation and delithiation during discharge.
[0040] Hereinafter, a negative electrode for a lithium metal battery, a lithium metal battery including the same, and a method of preparing the negative electrode for a lithium metal battery according to embodiments will be described in more detail.
[0041] [Negative electrode] According to one embodiment, a negative electrode for a lithium metal battery may include a negative electrode current collector and a protective layer disposed on the negative electrode current collector, wherein the protective layer includes a first protective layer and a second protective layer disposed between the first protective layer and the negative electrode current collector, the first protective layer includes porous nanostructured particles, and the second protective layer includes polar inorganic particles.
[0042] Since the first protective layer includes porous nanostructured particles, the first protective layer can selectively transmit lithium ions, so that the electrolyte and lithium ions can be prevented from contacting the negative electrode active material layer together. When the organic solvent and lithium ions contact lithium metal together, the organic solvent may decompose due to the reaction with lithium metal. Since lithium ions can selectively pass through the first protective layer through the pores of the porous nanostructured particles, the direct contact between the organic solvent and lithium metal can be effectively suppressed. Since the second protective layer includes polar inorganic particles, lithium ions can be uniformly distributed inside the second protective layer and at the interface between the second protective layer and the negative electrode current collector through the polar inorganic particles. Therefore, the local current density imbalance between the second protective layer and the negative electrode current collector can be suppressed, so that lithium metal can be uniformly plated between the second protective layer and the negative electrode current collector. Lithium metal can be uniformly plated between the second protective layer and the negative electrode current collector, thereby effectively suppressing the precipitation and / or growth of lithium dendrites caused by the local current density imbalance between the second protective layer and the negative electrode current collector. Since the second protective layer includes polar inorganic particles, it is possible to increase the uniformity of lithium ion distribution within the second protective layer and / or between the second protective layer and the negative electrode current collector.
[0043] Reference Figure 1 The negative electrode 20 may include a negative electrode current collector 21 and a protective layer 22 disposed on the negative electrode current collector 21, wherein the protective layer 22 includes a first protective layer 22a and a second protective layer 22b disposed between the first protective layer 22a and the negative electrode current collector 21, the first protective layer 22a includes porous nanostructured particles, and the second protective layer 22b includes polar inorganic particles.
[0044] Reference Figure 2The negative electrode 20 may include a negative electrode current collector 21 and a protective layer 22 disposed on the negative electrode current collector 21, wherein the protective layer 22 includes a first protective layer 22a and a second protective layer 22b disposed between the first protective layer 22a and the negative electrode current collector 21, the first protective layer 22a includes porous nanostructured particles, the second protective layer 22b includes polar inorganic particles, and the negative electrode 20 includes a negative electrode active material layer 23 disposed between the second protective layer 22 and the negative electrode current collector 21, wherein the negative electrode active material layer 23 includes lithium metal or a lithium alloy.
[0045] [Negative electrode: protective layer] Reference Figures 1 to 4 , the negative electrode 20 may include a negative electrode current collector 21 and a protective layer 22 disposed on the negative electrode current collector 21. The protective layer 22 may include a first protective layer 22a and a second protective layer 22b.
[0046] The first protective layer 22a includes porous nanostructured particles. The porous nanostructured particles may have a nanostructure in which a plurality of nanopores are arranged in the particles. Since the porous nanostructured particles include nanopores, lithium ions can be selectively transmitted through the nanopores, thereby effectively blocking the contact between the organic solvent and the negative electrode active material layer 23. The nanopores may have a size of 10 nm or less. The nanopores may have a size of, for example, about 0.1 nm to about 10 nm, about 0.1 nm to about 5 nm, about 0.1 nm to about 2 nm, or about 0.1 nm to about 1.0 nm. When the nanopores have a size within such a range, the selectivity for lithium ions can be improved. Therefore, the protective layer 22 can selectively transmit lithium ions included in the electrolyte, and the side reactions of the organic solvent can be effectively suppressed.
[0047] The porous nanostructured particles may include nanopores, and for example, the nanopores may be arranged regularly and / or periodically. The nanopores may be arranged regularly and / or periodically, and the first protective layer 22a may provide uniform lithium selectivity and / or uniform current density. Therefore, the first protective layer 22a may more effectively suppress side reactions caused by organic solvents and / or electrolytes. For example, negative ions may be arranged on the surface of the nanopores. Among the cations and anions constituting the porous nanostructured particles, the anions may constitute the surface area of the nanopores. Therefore, a portion or all of the surfaces of the nanopores included in the porous nanostructured particles may be negatively charged. That is, the surfaces of the nanopores included in the porous nanostructured particles may be anionic. Therefore, lithium cations may be more effectively transported through the nanopores.
[0048] The porous nanostructured particles may include, for example, metal organic frameworks (MOFs), polyhedral oligomeric silsesquioxanes (POSS), nanoporous silicon, nanoporous oxynitride, or a combination thereof, but one or more embodiments are not limited thereto. Any material available in the art as porous nanostructured particles may be used.
[0049] Due to the interaction between metal atoms and organic ligands, MOF has a porous coordination network structure with a high surface area. Although not particularly limited, MOF is a structure in which metal atoms (e.g., metal ions) and organic ligands having two or more coordination functional groups are continuously bonded. MOF is generally a porous body having a plurality of pores therein. MOF may include any functional molecule in the pores. One or more embodiments are not particularly limited thereto, and examples of metal atoms constituting MOF may include copper, iron, zinc, cobalt, niobium, zirconium, cadmium, nickel, chromium, vanadium, titanium, molybdenum, zirconium, aluminum, or a combination thereof. One or more metal atoms may constitute MOF. Examples of metal ions constituting metal-organic frameworks may include Cu, O, Zn, Nb, Ni, Zr, Cd, Ni, Zr, V, Ti, Mo, Zr, Al, or combinations thereof. 2+ , Fe 2+ / Fe 3+ 、Mo 2+ Cr 2+ 、Ru 2+ / Ru 3+ 、Mo 6+ , Li + 、Na + , K + , Rb + 、Be 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Sc 3+ , Y 3+ 、Ti 4+ 、Zr 4+ , Hf 4+ 、V 4+ 、V 3+ 、V 2 + , Nb 3+ 、 3+ Cr 3+ 、Mo 3+ , W 3+ , Mn 3+ , Mn 2+ 、Re 3+ 、Re 2+ , Fe 3+ , Fe 2+ 、Ru 3+ 、Ru 2+ , Os 3+ , Os2+ 、Co 3+ 、Co 2+ 、Rh 2 + 、Rh + 、Ir 2+ 、Ir + ,Knee 2+ ,Knee + 、Pd 2+ 、Pd + 、Pt 2+ 、Pt + 、Cu + 、Ag + 、Au + 、Zn 2+ 、Cd 2+ 、Hg 2+ 、B 3+ 、B 5+ 、Al 3+ 、Ga 3+ ,His 3+ ,Tea 3+ ,See 4+ ,See 2+ 、Ge 4+ 、Ge 2+ 、Sn 4+ 、Sn 2+ 、Pb 4+ 、Pb 2+ ,As 5+ ,As 3+ ,As + 、Sb 5+ 、Sb 3+ 、Sb + ,Be 5+ ,Be 3+ ,Be +or a combination thereof. The coordination functional group of the organic ligand may be a functional group capable of coordinating with a metal atom, and examples thereof may include a carboxyl group, an imidazole group, a hydroxyl group, a sulfonic acid group, a pyridyl group, a tertiary amine group, an amide group, a thioamide group, or a combination thereof. The organic ligand may include, for example, an organic ligand in which two or more coordination functional groups are substituted by a skeleton having a rigid structure (e.g., an aromatic ring or an unsaturated bond). Examples of the organic ligand may include benzene-1,3,5-tricarboxylic acid (BTC), 1,3,5-tris(4-carboxyphenyl)benzene (BTB), 1,4-benzenedicarboxylic acid (BDC), 2,5-dihydroxy-1,4-benzenedicarboxylic acid (DOBDC), cyclobutyl-1,4-benzenedicarboxylic acid (CBBDC), 2-amino-1,4-benzenedicarboxylic acid (H2N BDC), tetrahydropyrene 2,7-dicarboxylic acid (HPDC), terphenyl dicarboxylic acid (TPDC), 2,6-naphthalene dicarboxylic acid (2,6-NDC), pyrene 2,7-dicarboxylic acid (PDC), biphenyl dicarboxylic acid (BPDC), any dicarboxylic acid having a phenyl compound, 3,3',5,5'-biphenyltetracarboxylic acid, imidazole, benzimidazole, 2-nitroimidazole, cyclobenzimidazole, imidazole-2-carboxaldehyde, 4-cyanoimidazole, 6-methylbenzimidazole, 6-bromobenzimidazole, or a combination thereof.Examples of MOFs may include MIL-53, MIL-68, MIL-100 (Fe), MIL-101 (Cr), MOF 801, CAU-10H, MOF 808, IR-MOF-8, CPO-Ni-27, aluminum fumarate, MOF 199, DMOF (Zn), DUT-4, MOF-199 (HKUST-1) represented by Cu-BTC, MOF-177 represented by Zn4O (1,3,5-benzenetribenzoate)2, MOF-5 represented by Zn4O (1,4-benzenedicarboxylate)3 and also referred to as IRMOF-I, MOF-74 (Mg) represented by Mg2 (2,5-dihydroxy-1,4-benzenedicarboxylate), MOF-8 represented by Zn2 (2,5-dihydroxy-1,4-benzenedicarboxylate), MOF-9 represented by Zn2 (1,3,5-dihydroxy-1,4-benzenedicarboxylate), MOF-100 (Fe), MOF-101 (Cr), MOF-102 (Fe), MOF-103 (Mg) represented by Zn2 (1,3,5-dihydroxy-1,4-benzenedicarboxylate), MOF-104 (Mg) represented by Zn2 (1,3,5-dihydroxy-1,4-benzenedicarboxylate), MOF-105 (Mg) represented by Zn2 (1,3,5-dihydroxy-1,4-benzenedicarboxylate), MOF-106 (Mg) represented by Zn2 (1,3,5-dihydroxy-1,4-benzenedicarboxylate), MOF-107 (Mg) represented by Zn2 (1,3,5-dihydroxy-1,4-benzenedicarboxylate), MOF-108 (Mg) represented by Zn2 (1,3,5-dihydroxy-1,4-benzened MOF-74 (Zn) represented by Zn4O (hydroxy-1,4-benzenedicarboxylate), MOF-505 represented by Cu2 (3,3',5,5'-biphenyltetracarboxylate), IRMOF-6 represented by Zn4O (cyclobutyl-1,4-phthalate), IRMOF-3 represented by Zn4O (2-amino-1,4-phthalate), 1 represented by Zn4O (terphenyl dicarboxylate)3 or Zn4O (tetrahydropyrene 2,7-dicarboxylate), RMOF-11, IRMOF-8 represented by Zn4O(tetrahydropyrene 2,7-dicarboxylate)3, ZIF-68 represented by Zn(benzimidazole ester)(2-nitroimidazole ester), ZIF-69 represented by Zn(cyclobenzimidazole ester)(2-nitroimidazole ester), ZIF-7 represented by Zn(benzimidazole ester)2, ZIF-9 represented by Co(benzimidazole ester)2, ZIF-11 represented by Zn2(benzimidazole ester), Zn( The invention relates to a kind of MOF, and the ... Examples of porous oxide-based materials derived from MOF may include iron oxide-based materials such as iron-containing Fe2O3 derived from MIL100(Fe).
[0050] The porous nanostructured particles may have a size of, for example, about 100 nm to about 5 μm, about 200 nm to about 3 μm, about 200 nm to about 2 μm, about 200 nm to about 1.5 μm, or about 500 nm to about 1.5 μm. Since the porous nanostructured particles have a size within such a range, the cycle characteristics of a lithium metal battery using a protective layer including the porous nanostructured particles can be further improved.
[0051] The content of the porous nanostructured particles may be, for example, in the range of about 50 wt % to about 99 wt %, about 60 wt % to about 95 wt %, or about 70 wt % to about 90 wt % relative to the total weight of the first protective layer 22 a. When the first protective layer 22 a includes the porous nanostructured particles within such a content range, the lithium ion selectivity of the first protective layer 22 a can be further improved and the side reaction of the electrolyte can be further suppressed.
[0052] Reference Fig.10 , the surface of the first protective layer 22a may include protrusions and depressions. The protrusions may be formed by porous nanostructured particles. The depressions may be formed by pores between a plurality of adjacent porous nanostructured particles. Since the surface of the first protective layer 22a includes protrusions and depressions, the first protective layer 22a may maintain a large contact area with the electrolyte, and the adhesion between the negative electrode and the electrolyte layer may be improved. Therefore, it is possible to prevent deterioration such as lithium dendrite growth caused by peeling between the negative electrode and the electrolyte layer during the charge / discharge process of the lithium metal battery.
[0053] The first protective layer 22a may include a first binder. The first binder may include, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride (PVDF), polyethylene (PE), vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but one or more embodiments are not necessarily limited thereto. Any material that can be used as a binder in the art can be used. The first binder can be provided as a single binder or a plurality of different binders. When the first protective layer 22a does not include the first binder, the first protective layer 22a will be easily separated from the second protective layer 22b and / or the negative electrode current collector 21. The first binder may be, for example, a fluorine-based binder. The fluorine-based binder may include, for example, polytetrafluoroethylene, PVDF, vinylidene fluoride / hexafluoropropylene copolymer, etc. With respect to about 100 parts by weight of the porous nanostructured particles, the first protective layer 22a may include, for example, a first binder having a content of about 1 part by weight to about 50 parts by weight, about 5 parts by weight to about 45 parts by weight, or about 10 parts by weight to about 45 parts by weight. The content of the first binder may be, for example, in the range of about 1 wt% to about 50 wt% relative to the total weight of the first protective layer 22a. The first binder may have a weight average molecular weight of about 300,000 Daltons to about 1,000,000 Daltons, or about 400,000 Daltons to about 600,000 Daltons. The weight average molecular weight of the first binder may be measured, for example, using gel permeation chromatography (GPC) on a polystyrene standard sample.
[0054] The second protective layer 22b may include polar inorganic particles. The polar inorganic particles may have a dielectric constant (relative dielectric constant) of, for example, 5.0 or greater, 6.0 or greater, 7.0 or greater, 8.0 or greater, or 9.0 or greater. The polar inorganic particles may have a dielectric constant of, for example, about 5 to about 30, about 6 to about 30, about 7 to about 30, about 8 to about 30, or about 9 to about 30. Since the polar inorganic particles have such a high dielectric constant, lithium ions can be evenly distributed in the second protective layer 22b, and the diffusion rate of lithium ions can be increased. It is possible to prevent the local current density in the second protective layer 22b from being unbalanced. In addition, lithium metal can be evenly plated at the interface between the second protective layer 22b and the negative electrode current collector 21 or at the interface between the second protective layer 22b and the negative electrode active material layer 23, and the generation and / or precipitation of lithium dendrites can be suppressed. The polar inorganic particles may have, for example, crystallinity. The crystallinity of the polar inorganic particles can be, for example, 50% or more, 60% or more, 70% or more, or 80% or more. The crystallinity is the ratio of the crystalline part to the whole inorganic particles. The crystallinity of the polar inorganic particles can be calculated by, for example, the intensity ratio of the X-ray diffraction (XRD) peak intensity of the polar inorganic particles to be analyzed to the XRD peak intensity of the polar inorganic particles with 100% crystallinity.
[0055] The polar inorganic particles can be, for example, nanoparticles having a size of less than 1 μm. Since the polar inorganic particles are nanoparticles having such a size, the uniformity of the lithium ion distribution in the second protective layer 22b can be further improved. When the particle size of the polar inorganic particles is excessively increased, it may be difficult to improve the uniformity of the lithium ion distribution in the second protective layer 22b. The polar inorganic particles can have a size of, for example, about 10 nm to about 900 nm, about 10 nm to about 700 nm, about 10 nm to about 500 nm, about 10 nm to about 400 nm, or about 10 nm to about 200 nm. Since the polar inorganic particles have a particle size within such a range, the distribution uniformity of the lithium ions in the second protective layer 22b can be further improved.
[0056] The size of the polar inorganic particles can be smaller than, for example, the size of the porous nanostructured particles. The size of the polar inorganic particles can be, for example, 50% or less of the size of the porous nanostructured particles. The size of the polar inorganic particles can be, for example, in the range of about 1% to about 50%, about 1% to about 40%, about 1% to about 30%, about 5% to about 30%, or about 5% to about 20% of the size of the porous nanostructured particles. Since the size of the polar inorganic particles is smaller than the size of the porous nanostructured particles, the second protective layer 22b including the polar inorganic particles can form a uniform interface with the negative electrode current collector 21 and / or the negative electrode active material layer 23 as compared with the first protective layer 22a including the porous nanostructured particles. Therefore, the second protective layer 22b can more effectively inhibit the generation or growth of lithium dendrites at the interface between the second protective layer 22b and the negative electrode current collector 21 and / or between the second protective layer 22b and the negative electrode active material layer 23.
[0057] Examples of the polar inorganic particles can include LiF, LiOH, Li2O, Li2CO3, Li3PO4, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2, HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, SiC, Li 3+x La3M2O 12 (where M = Te, Nb or Zr, and 0 ≤ x ≤ 5), Li 1+x+y Al x Ti 2- x Si y P 3-y O 12 (where 0 < x < 2 and 0 ≤ y < 3), BaTiO3, Pb(Zr p Ti 1-p) O3 (PZT) (where 0 ≤ p ≤ 1), Pb 1- x La x Zr 1-y Ti y O3 (PLZT) (where 0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg 1 / 3 Nb 2 / 3 ) O3 - PbTiO3 (PMN - PT), Li x Ti y (PO4)3 (where 0 < x < 2 and 0 < y < 3), Li x Al y Ti z (PO4)3 (where 0 < x < 2, 0 < y < 1 and 0 < z < 3), Li 1+x+y (Al p Ga 1-p ) x (Ti q Ge 1-q ) 2-x Si y P 3-y O 12 (where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ p ≤ 1 and 0 ≤ q ≤ 1), Li x La y TiO3 (where 0 < x < 2 and 0 < y < 3), Li x Ge y P z S w (where 0 < x < 4, 0 < y < 1, 0 < z < 1 and 0 < w < 5), Li x N y (where 0 < x < 4 and 0 < y < 2), Li x Si y S z (where 0 < x < 3, 0 < y < 2 and 0 < z < 4), Li x P y S z (where 0 ≤ x < 3, 0 < y < 3 and 0 < z < 7) or combinations thereof, but one or more embodiments are not necessarily limited thereto. Any material available in the art that can be used as polar inorganic particles can be used.
[0058] The content of the polar inorganic particles may be, for example, in the range of about 1 wt % to about 50 wt %, about 5 wt % to about 40 wt %, or about 10 wt % to about 30 wt % relative to the total weight of the second protective layer 22 b. Since the second protective layer 22 b includes the polar inorganic particles in such a content range, the distribution uniformity of lithium ions in the second protective layer 22 b can be improved, and the generation and / or growth of lithium dendrites can be more effectively suppressed.
[0059] The second protective layer 22b may include a second binder. The second binder may include, for example, SBR, polytetrafluoroethylene, PVDF, PE, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but one or more embodiments are not necessarily limited thereto. Any material that can be used as a binder in the art can be used. The second binder may be provided as a single binder or a plurality of different binders. When the second protective layer 22b does not include a second binder, the second protective layer 22b will be easily separated from the first protective layer 22a and / or the negative electrode current collector 21. The second binder may be, for example, a fluorine-based binder. Fluorine-based binders may include, for example, polytetrafluoroethylene, PVDF, vinylidene fluoride / hexafluoropropylene copolymer, etc. Relative to about 100 parts by weight of polar inorganic particles, the second protective layer 22b may include, for example, a second binder having a content of about 100 parts by weight to about 1,000 parts by weight, about 100 parts by weight to about 500 parts by weight, or about 100 parts by weight to about 300 parts by weight. Relative to the total weight of the second protective layer 22b, the content of the second binder can be, for example, in the range of about 50wt% to about 90wt%. The second binder disposed in the second protective layer 22b can be the same as or different from the first binder disposed in the first protective layer 22a. The second binder can have a weight average molecular weight of about 300,000 Daltons to about 1,000,000 Daltons, or about 400,000 Daltons to about 600,000 Daltons. The weight average molecular weight of the second binder can be measured, for example, using GPC on a polystyrene standard sample.
[0060] The first protective layer 22a may have a thickness of, for example, about 100 nm to about 20 μm, about 500 nm to about 20 μm, about 1 μm to about 20 μm, or about 1 μm to about 15 μm. When the first protective layer 22a has a thickness within such a range, the decomposition of the electrolyte can be more effectively suppressed, thereby further improving the cycle characteristics of the lithium metal battery including the first protective layer 22a. The second protective layer 22b may have a thickness of, for example, about 100 nm to about 15 μm, about 500 nm to about 15 μm, about 1 μm to about 15 μm, or about 1 μm to about 10 μm. When the second protective layer 22b has a thickness within such a range, the distribution uniformity of lithium ions can be improved, and the cycle characteristics of the lithium metal battery including the second protective layer 22b can be further improved. The protective layer 22 may have a total thickness of, for example, about 200 nm to about 25 μm, about 500 nm to about 25 μm, about 2 μm to about 25 μm, or about 2 μm to about 20 μm. When the protective layer 22 has a thickness within such a range, it is possible to effectively suppress the decomposition of the electrolyte and suppress the local current density imbalance, thereby effectively preventing the generation and / or growth of lithium dendrites. Therefore, the cycle characteristics of the lithium metal battery including the protective layer 22 can be further improved. When the thickness of the protective layer 22 is excessively increased, the energy density of the lithium metal battery may be reduced. When the thickness of the protective layer 22 is excessively reduced, the improvement in the cycle characteristics of the lithium metal battery may not be significant.
[0061] The thickness of the second protective layer 22b may be less than the thickness of the first protective layer 22a. The thickness of the second protective layer 22b may be 95% or less or 90% or less of the thickness of the first protective layer 22a. The thickness of the second protective layer 22b may be in the range of about 10% to about 95%, about 30% to about 95%, about 50% to about 95%, or about 70% to about 95% of the thickness of the first protective layer 22a. Since the thickness of the second protective layer 22b is less than the thickness of the first protective layer 22a, the overall structural strength of the protective layer 22 can be improved, and the durability of the protective layer 22 can be improved.
[0062] Reference Figure 3 and Figure 4 , the protective layer 22 may be additionally disposed on the side surface of the negative electrode active material layer 23 and / or the negative electrode current collector 21 .
[0063] Reference Figure 3, the negative electrode 20 may include a negative electrode current collector 21 and a protective layer 22 disposed on the negative electrode current collector 21, wherein the protective layer 22 includes a first protective layer 22a and a second protective layer 22b disposed between the first protective layer 22a and the negative electrode current collector 21, the first protective layer 22a includes porous nanostructured particles, the second protective layer 22b includes polar inorganic particles, and the protective layer 22 is configured to extend to at least one side surface of the negative electrode current collector 21. The protective layer 22 may be configured to extend to the side surface of the negative electrode current collector 21. The protective layer 22 may completely cover the side surface of the negative electrode current collector 21. The protective layer 22 may be configured to extend to at least one side surface of the negative electrode current collector 21, thereby more effectively protecting the lithium metal layer plated between the protective layer 22 and the negative electrode current collector 21.
[0064] Reference Figure 4 , the negative electrode 20 may include a negative electrode current collector 21 and a protective layer 22 disposed on the negative electrode current collector 21, wherein the protective layer 22 includes a first protective layer 22a and a second protective layer 22b disposed between the first protective layer 22a and the negative electrode current collector 21, the first protective layer 22a includes porous nanostructured particles, the second protective layer 22b includes polar inorganic particles, the negative electrode active material layer 23 includes lithium metal or lithium alloy, and the protective layer 22 is configured to extend to at least one side surface of the negative electrode active material layer 23 and / or the negative electrode current collector 21. The protective layer 22 may completely cover the negative electrode active material layer 23 and may extend to the side surface of the negative electrode current collector 21. The protective layer 22 may completely cover the side surface of the negative electrode active material layer 23 and / or the negative electrode current collector 21. Since the protective layer 22 extends to at least one side surface of the negative electrode active material layer 23 and / or the negative electrode current collector 21, the negative electrode active material layer 23 may be more effectively protected.
[0065] [Negative electrode: negative electrode active material layer] Reference Figure 2 and Figure 4 The negative electrode 20 may further include a negative electrode active material layer 23 disposed between the negative electrode current collector 21 and the protective layer 22. The negative electrode active material layer 23 may include, for example, lithium metal or a lithium alloy.
[0066] The negative electrode active material layer 23 may include, for example, lithium foil, lithium powder, plated lithium, carbon-based materials, or a combination thereof. The negative electrode active material layer including lithium foil may be, for example, a lithium metal layer. The negative electrode active material layer including lithium powder may be prepared by applying a slurry including lithium powder, a binder, etc. to the negative electrode current collector. The binder may be, for example, a fluorine-based binder such as PVDF. The negative electrode active material layer 23 may not include a carbon-based negative electrode active material. Therefore, the negative electrode active material layer 23 may be made of a metal-based negative electrode active material. The negative electrode active material layer 23 may also be a plated lithium metal layer. A lithium metal layer plated between the negative electrode current collector 21 and the protective layer 22 by charging after assembling the negative electrode 20, the positive electrode, and the electrolyte that do not include the negative electrode active material layer 23 to manufacture a lithium battery may be further included as the negative electrode active material layer 23.
[0067] The negative electrode active material layer 23 may have a thickness of, for example, about 0.1 μm to about 100 μm, about 0.1 μm to about 80 μm, about 1 μm to about 80 μm, or about 10 μm to about 80 μm, but one or more embodiments are not necessarily limited to such a range. The thickness of the negative electrode active material layer 23 may be adjusted according to the desired shape, capacity, etc. of the lithium metal battery. When the thickness of the negative electrode active material layer 23 is excessively increased, the structural stability of the lithium metal battery may deteriorate, and side reactions may increase. When the thickness of the negative electrode active material layer 23 is excessively reduced, the energy density of the lithium metal battery may decrease. The lithium foil may have a thickness of, for example, about 1 μm to about 50 μm, about 1 μm to about 30 μm, about 10 μm to about 30 μm, or about 10 μm to about 80 μm. When the lithium foil has a thickness within such a range, the life characteristics of the lithium battery including the protective layer can be further improved. The lithium powder may have a particle size of, for example, about 0.1 μm to about 3 μm, about 0.1 μm to about 2 μm, or about 0.1 μm to about 2 μm. When the lithium powder has a particle size within such a range, the life characteristics of the lithium battery including the protective layer can be further improved. The plated lithium metal layer may have a thickness of, for example, about 1 μm to about 80 μm, or about 10 μm to about 80 μm.
[0068] [Negative electrode: negative electrode current collector] Reference Figures 1 to 4 , the negative electrode 20 may include a negative electrode current collector 21 .
[0069] The negative electrode current collector 21 may include, for example, a first metal substrate. The first metal substrate may include a first metal as a main component or may be made of a first metal. The content of the first metal included in the first metal substrate may be, for example, 90 wt% or more, 95 wt% or more, 99 wt% or more, or 99.9 wt% or more relative to the total weight of the first metal substrate. The first metal substrate may be made of, for example, a material that does not react with lithium (i.e., does not form an alloy and / or compound with lithium). Examples of the first metal may include copper (Cu), nickel (Ni), stainless steel (SUS), iron (Fe), and cobalt (Co), but one or more embodiments are not necessarily limited thereto. Any material that can be used as a current collector in the art may be used. The first metal substrate may be made of, for example, one of the above metals or an alloy of two or more metals. The first metal substrate may be in the form of, for example, a sheet or foil. The negative electrode current collector 21 may have, for example, a thickness of about 5 μm to about 50 μm, about 10 μm to about 50 μm, about 10 μm to about 40 μm, or about 10 μm to about 30 μm, but one or more embodiments are not necessarily limited to such a range. The thickness of the negative electrode current collector 21 may be adjusted according to the desired shape, capacity, etc. of the lithium metal battery.
[0070] The negative electrode current collector 21 may further include a coating layer (not shown) including a second metal on the first metal substrate.
[0071] The negative electrode current collector 21 may include, for example, a first metal substrate and a coating layer disposed on the first metal substrate and including a second metal. The second metal has a Mohs hardness higher than that of the first metal. That is, since the coating layer including the second metal is harder than the substrate including the first metal, degradation of the first metal substrate can be prevented. The material constituting the first metal substrate may have, for example, a Mohs hardness of 5.5 or less. The first metal may, for example, have a Mohs hardness of 5.5 or less, 5.0 or less, 4.5 or less, 4.0 or less, 3.5 or less, or 3.0 or less. The first metal may have, for example, a Mohs hardness of about 2.0 to about 6.0. The coating layer may include the second metal. The coating layer may include, for example, the second metal as a main component or may be made of the second metal. Relative to the total weight of the coating layer, the content of the second metal included in the coating layer may, for example, be in the range of 90wt% or more, 95wt% or more, 99wt% or more, or 99.9wt% or more. The coating layer may be made of, for example, a material that does not react with lithium (ie, does not form an alloy and / or compound with lithium). The material constituting the coating layer may have, for example, a Mohs hardness of 6.0 or greater. For example, the second metal may have a Mohs hardness of 6.0 or greater, 6.5 or greater, 7.0 or greater, 7.5 or greater, 8.0 or greater, 8.5 or greater, or 9.0 or greater. The second metal may have, for example, a Mohs hardness of about 6.0 to about 12. When the Mohs hardness of the second metal is too low, it may be difficult to suppress the degradation of the negative electrode current collector 21. When the Mohs hardness of the second metal is too high, the processing of the second metal may not be easy. The second metal may include, for example, at least one selected from titanium (Ti), manganese (Mn), niobium (Nb), tantalum (Ta), iridium (Ir), vanadium (V), rhenium (Re), osmium (Os), tungsten (W), chromium (Cr), boron (B), ruthenium (Ru) and rhodium (Rh). The coating layer may be made of, for example, one of the above metals or an alloy of two or more metals. The Mohs hardness difference between the first metal included in the first metal substrate and the second metal included in the coating layer may be, for example, 2 or more, 2.5 or more, 3 or more, 3.5 or more, or 4 or more. When the first metal and the second metal have such a Mohs hardness difference, the degradation of the negative electrode current collector 21 can be further suppressed. The coating layer may have a single-layer structure or a multilayer structure including two or more layers. The coating layer may have, for example, a two-layer structure including a first coating layer and a second coating layer. The coating layer may have, for example, a three-layer structure including a first coating layer, a second coating layer, and a third coating layer. The coating layer may have, for example, a thickness of about 10 nm to about 1 μm, 50 nm to 500 nm, 50 nm to 200 nm, or 50 nm to 150 nm. When the coating layer is too thin, it may be difficult to suppress the uneven growth of the lithium-containing metal layer. As the thickness of the coating layer increases, the cycle characteristics of the lithium battery can be improved.However, when the coating layer is too thick, the energy density of the lithium battery may be reduced, and it may not be easy to form the coating layer. The coating layer can be provided on the first metal substrate by, for example, vacuum deposition, sputtering, plating, etc., but one or more embodiments are not necessarily limited to such methods. Any method capable of forming the coating layer in the art can be used.
[0072] Although not shown in the drawings, the negative electrode current collector 21 may include, for example, a base film and a metal layer disposed on one or both surfaces of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. Since the base film includes an insulating thermoplastic polymer, when a short circuit occurs, the base film may soften or liquefy to block the operation of the battery, thereby suppressing the rapid increase of the current. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The metal layer may correspond to, for example, a first metal substrate. The metal layer may further include a coating layer containing a second metal. The negative electrode current collector 21 may further include a metal sheet and / or a lead tab. For more specific details of the base film, metal layer, metal sheet, and lead tab of the negative electrode current collector 21, refer to the positive electrode current collector. Since the negative electrode current collector 21 has such a structure, the weight of the negative electrode can be reduced, thereby improving the energy density of the negative electrode and the lithium battery.
[0073] [Negative electrode: negative electrode intermediate layer] Reference Figure 1 and Figure 3 The negative electrode 20 may further include a negative electrode intermediate layer (not shown) disposed between the negative electrode current collector 21 and the protective layer 22. Figure 2 and Figure 4 The negative electrode 20 may further include a negative electrode intermediate layer (not shown) disposed between the protective layer 22 and the negative electrode active material layer 23. Since the negative electrode 20 additionally includes the negative electrode intermediate layer, the generation and / or growth of lithium dendrites in the negative electrode 20 can be more effectively suppressed. The negative electrode intermediate layer may be omitted.
[0074] The negative electrode intermediate layer may include, for example, a negative electrode active material and a binder. The negative electrode active material may be a negative electrode material that can be lithiated and delithiated. The negative electrode active material included in the negative electrode intermediate layer may have, for example, a particle form. The negative electrode active material in particle form may have, for example, an average particle size of about 10 nm to about 4 μm, about 10 nm to about 1 μm, about 10 nm to about 500 nm, about 10 nm to about 100 nm, or about 20 nm to about 80 nm. Since the negative electrode active material has an average particle size within such a range, reversible plating and / or dissolution of lithium can be more easily performed during charge / discharge. The average particle size of the negative electrode active material is, for example, a median particle size (D50) measured using a laser particle size distribution meter.
[0075] The negative electrode active material included in the negative electrode intermediate layer may include, for example, at least one selected from a carbon-based negative electrode active material and a metal or metalloid negative electrode active material. The carbon-based negative electrode active material may be, for example, amorphous carbon. Examples of carbon-based negative electrode active materials may include carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, etc., but one or more embodiments are not necessarily limited thereto. Any material classified as amorphous carbon in the art may be used. Amorphous carbon may be carbon that has no crystallinity or has very low crystallinity, and may be distinguished from crystalline carbon or graphite-based carbon. The metal or metalloid negative electrode active material may include at least one selected from gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn), but one or more embodiments are not necessarily limited thereto. Any material used as a metal negative electrode active material or a metalloid negative electrode active material in the art and forming an alloy or compound with lithium may be used. For example, nickel (Ni) does not form an alloy with lithium and is therefore not a metal negative electrode active material in this specification. The negative electrode intermediate layer may include one type of negative electrode active material among such negative electrode active materials or a mixture of multiple different negative electrode active materials. The negative electrode intermediate layer may include, for example, a mixture of amorphous carbon and at least one selected from gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). The mixing ratio of the mixture may be, for example, a weight ratio of about 10:1 to about 1:2, about 10:1 to about 1:1, about 7:1 to about 1:1, about 5:1 to about 1:1, or about 4:1 to about 2:1. The negative electrode active material included in the negative electrode intermediate layer may include, for example, a mixture of first particles including amorphous carbon and second particles including metal or metalloid. Examples of metals may include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), etc. The content of the second particles may be in the range of about 8 wt % to about 60 wt %, about 10 wt % to about 50 wt %, about 15 wt % to about 40 wt %, or about 20 wt % to about 30 wt % relative to the total weight of the mixture. Since the second particles are included in the content within such a range, for example, the cycle characteristics of the lithium battery may be further improved.
[0076] The binder included in the negative electrode intermediate layer may include, for example, SBR, polytetrafluoroethylene, PVDF, PE, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but one or more embodiments are not necessarily limited thereto. Any material that can be used as a binder in the art can be used. The binder can be provided as a single binder or a plurality of different binders. When the negative electrode intermediate layer does not include a binder, the negative electrode intermediate layer can be easily separated from the protective layer 22 or the negative electrode current collector 21. Relative to the gross weight of the negative electrode intermediate layer, the content of the binder included in the negative electrode intermediate layer can be, for example, in the range of about 1wt% to about 20wt%.
[0077] The negative electrode intermediate layer may have a thickness of, for example, about 1 μm to about 20 μm, about 1 μm to about 15 μm, about 2 μm to about 10 μm, or about 3 μm to about 7 μm. The thickness of the negative electrode intermediate layer may be, for example, in the range of about 1% to about 50%, about 1% to about 30%, about 1% to about 10%, or about 1% to about 5% of the thickness of the positive electrode active material layer. When the negative electrode intermediate layer is too thin, the lithium dendrites formed between the negative electrode intermediate layer and the negative electrode current collector may collapse the negative electrode intermediate layer, which may make it difficult to improve the cycle characteristics of the lithium battery. When the thickness of the negative electrode intermediate layer is excessively increased, the energy density of the lithium battery using the negative electrode 20 may be reduced, and its cycle characteristics may be difficult to improve. For example, when the thickness of the negative electrode intermediate layer is reduced, the charge capacity of the negative electrode intermediate layer may also be reduced. The charge capacity of the negative electrode intermediate layer may be, for example, in the range of about 0.1% to about 50%, about 1% to about 30%, about 1% to about 10%, about 1% to about 5%, or about 1% to about 2% of the charge capacity. When the charge capacity of the negative electrode intermediate layer is too low, the lithium dendrites formed between the negative electrode intermediate layer and the negative electrode current collector may collapse the negative electrode intermediate layer, which may make it difficult to improve the cycle characteristics of the lithium battery. When the charge capacity of the negative electrode intermediate layer is excessively increased, the energy density of the lithium battery using the negative electrode 20 may be reduced, and its cycle characteristics may be difficult to improve. The charge capacity of the positive electrode active material layer is obtained by multiplying the charge capacity density (mAh / g) of the positive electrode active material by the mass of the positive electrode active material in the positive electrode active material layer. When several types of positive electrode active materials are used, for each positive electrode active material, the value of the charge capacity density × mass is calculated, and the sum of the values is the charge capacity of the positive electrode active material layer. The charge capacity of the negative electrode intermediate layer is also calculated in the same way. That is, the charge capacity of the negative electrode intermediate layer is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the negative electrode intermediate layer. When several types of negative electrode active materials are used, for each negative electrode active material, the value of the charge capacity density × mass is calculated, and the sum of the values is the charge capacity of the negative electrode intermediate layer. Here, the charge capacity density of the positive electrode active material and the negative electrode active material is the capacity estimated using an all-solid half-cell using lithium metal as a counter electrode. The charge capacity of the positive electrode active material layer and the negative electrode intermediate layer is directly measured by measuring the charge capacity using an all-solid half-cell. When the measured charge capacity is divided by the mass of each active material, the charge capacity density is obtained. Alternatively, the charge capacity of the positive electrode active material layer and the negative electrode intermediate layer may be the initial charge capacity measured during the first cycle of charging.
[0078] [Lithium battery] A lithium battery according to one embodiment may include a positive electrode, the negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode. The lithium battery may include the negative electrode, and thus may have both improved capacity and excellent lifespan characteristics.
[0079] The lithium battery may be, for example, a lithium primary battery, a lithium secondary battery, a lithium sulfur battery, a lithium air battery, etc., but is not limited thereto. Any lithium battery used in the art may be used.
[0080] For example, a lithium battery may be manufactured by the following exemplary method, but one or more embodiments are not necessarily limited to such a method. The method may be adjusted according to required conditions.
[0081] (Negative electrode) Prepare the negative electrode as described above.
[0082] (Positive electrode) First, a positive electrode active material, a conductive agent, a binder and a solvent are mixed to prepare a positive electrode active material composition. The prepared positive electrode active material composition is directly applied to an aluminum current collector and dried to prepare a positive electrode plate having a positive electrode active material layer formed thereon. Alternatively, the positive electrode active material composition is cast on a separate support, and then the film obtained by peeling off the support is laminated on the aluminum current collector to prepare a positive electrode plate having a positive electrode active material layer formed thereon.
[0083] As the positive electrode active material, any material that is a lithium-containing metal oxide and is generally used in the art can be used without limitation. For example, at least one composite oxide of lithium and a metal selected from cobalt, manganese, nickel, and a combination thereof can be used. Specific examples of the positive electrode active material may include a compound represented by any one of the following formulas: Li a A 1-b B b D2 (where 0.90≤a≤1 and 0≤b≤0.5), Li a E 1-b B b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5 and 0≤c≤0.05), LiE 2-b B b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05), Li a Ni 1-b-c Co b B c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2), Lia Ni 1-b-c Co b B c O 2-α F α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2), Li a Ni 1-b-c Co b B c O 2-α F2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2), Li a Ni 1-b-c Mn b B c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2), Li a Ni 1-b-c Mn b B c O 2-α F α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2), Li a Ni 1-b- c Mn b B c O 2-α F2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2), Li a Ni b E c G d O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1), Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤.5 and 0.001≤e≤0.1), Li a NeG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1), Li a CoG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1), Li a MnG b O2 (where 0.90≤a≤1 and 0.001≤b≤0.1), Lia Mn b O4 (where 0.90≤a≤1 and 0.001≤b≤0.1), QO2, QS2, LiQS2, V2O5, LiV2O5, LiIO2, LiNiVO4, Li (3-f) J2(PO4)3 (where 0≤f≤2), Li (3-f) Fe2(PO4)3 (where 0≤f≤2) and LiFePO4.
[0084] In the formula representing the above-mentioned compound, A can be Ni, Co, Mn or a combination thereof, B can be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof, D can be O, F, S, P or a combination thereof, E can be Co, Mn or a combination thereof, F can be F, S, P or a combination thereof, G can be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof, Q can be Ti, Mo, Mn or a combination thereof, I can be Cr, V, Fe, Sc, Y or a combination thereof, and J can be V, Cr, Mn, Co, Ni, Cu or a combination thereof. Compounds in which a coating layer is added to the surface of the above-mentioned compound can also be used, and mixtures of the above-mentioned compound and compounds in which a coating layer is added can also be used. The coating layer added to the surface of the above-mentioned compound can include, for example, a coating element compound: an oxide or hydroxide of the coating element, an oxyhydroxide of the coating element, an oxygen-containing carbonate of the coating element, or a hydroxycarbonate of the coating element. The compound constituting the coating layer is amorphous or crystalline. The coating element included in the coating layer may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof. The method for forming the coating layer may be selected within the range that does not adversely affect the physical properties of the positive electrode active material. The coating method may include, for example, spraying, dipping, etc. Since the specific coating method can be well understood by those skilled in the art, its detailed description will be omitted.
[0085] The positive electrode active material may include, for example, Li a Ni x Co y M z O 2-b A b(where 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, x + y + z = 1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof), LiNi x Co y Mn z O2 (where 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2 and x + y + z = 1), LiNi x Co y Al z O2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2 and x + y + z = 1), LiNi x Co y Mn z Al w O2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, 0 < w ≤ 0.2 and x + y + z + w = 1), Li a Co x M y O 2-b A b (1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.9 ≤ x ≤ 1, 0 ≤ y ≤ 0.1, x + y = 1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof), Li a Ni x Mn y M' z O 2-b A b (1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0 < x ≤ 0.3, 0.5 ≤ y < 1, 0 < z ≤ 0.3, x + y + z = 1, M' is cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof), Li a M1 x M2 y PO 4-b X b(wherein, 0.90 ≤ a ≤ 1.1, 0 ≤ x ≤ 0.9, 0 ≤ y ≤ 0.5, 0.9 < x + y < 1.1, 0 ≤ b ≤ 2, M1 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), or a combination thereof, M2 is magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zinc (Zn), boron (B), niobium (Nb), gallium (Ga), indium (In), molybdenum (Mo), tungsten (W), aluminum (Al), silicon (Si), chromium (Cr), vanadium (V), scandium (Sc), yttrium (Y), or a combination thereof, and X is O, F, S, P, or a combination thereof), or Li a M3 z PO4 (0.90 ≤ a ≤ 1.1, 0.9 ≤ z ≤ 1.1, and M3 is chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr), or a combination thereof).
[0086] Examples of the conductive agent may include: CB, graphite particles, natural graphite, artificial graphite, acetylene black, KB, or carbon fiber; carbon nanotubes; metal powders, metal fibers, or metal tubes of copper, nickel, aluminum, or silver; and conductive polymers such as polyphenylene derivatives, but one or more embodiments are not limited thereto. Any material used as a conductive material in the art may be used. Optionally, the negative electrode may not include, for example, a separate conductive material.
[0087] Examples of the binder may include vinylidene fluoride / hexafluoropropylene copolymer, PVDF, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the above polymers, SBR-based polymers, etc. Examples of the solvent may include N-methylpyrrolidone (NMP), acetone, water, etc., but one or more embodiments are not necessarily limited thereto. Any material used in the art may be used.
[0088] A plasticizer or a pore-forming agent may be further added to the positive electrode active material composition to form pores in the electrode plate.
[0089] The contents of the positive electrode active material, conductive agent, binder, and solvent used in the positive electrode are at levels commonly used in lithium batteries. Depending on the use and structure of the lithium battery, one or more of the conductive material, binder, and solvent may be omitted.
[0090] Relative to the total weight of the positive electrode active material layer, the content of the binder included in the positive electrode may be in the range of about 0.1 wt % to about 10 wt %, or about 0.1 wt % to about 5 wt %. The content of the positive electrode active material included in the positive electrode may be in the range of about 80 wt % to about 99 wt %, about 90 wt % to about 99 wt %, or about 95 wt % to about 99 wt % of the total weight of the positive electrode active material layer.
[0091] The positive electrode current collector may include a plate, foil, etc. made of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector may have a thickness of, for example, about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 5 μm to about 25 μm, or about 10 μm to about 20 μm.
[0092] The positive electrode current collector may include, for example, a base film and a metal layer disposed on one or both surfaces of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, PET, PE, PP, PBT, PI, or a combination thereof. The base film may include, for example, an insulator. Since the base film includes an insulating thermoplastic polymer, when a short circuit occurs, the base film may soften or liquefy to block the operation of the battery, thereby suppressing the rapid increase of the current. The metal layer may include indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The metal layer may be used as an electrochemical fuse and may be cut off due to overcurrent to perform a short circuit prevention function. The limiting current and the maximum current may be adjusted by adjusting the thickness of the metal layer. The metal layer may be plated or deposited on the base film. When the thickness of the metal layer is reduced, the limiting current and / or the maximum current of the positive electrode may be reduced, thereby improving the stability of the lithium battery during a short circuit. Lead tabs can be added to the metal layer to connect to the outside. The lead tab can be welded to the metal layer or the metal layer / base film stack by ultrasonic welding, laser welding, spot welding, etc. While the base film and / or the metal layer melt during welding, the metal layer can be electrically connected to the lead tab. In order to more firmly weld the metal layer and the lead tab, a metal sheet can be added between the metal layer and the lead tab. The metal sheet can be a thin sheet of the same material as the metal of the metal layer. The metal sheet can be, for example, a metal foil or a metal mesh. The metal sheet can be, for example, an aluminum foil, a copper foil, or a SUS foil. The metal sheet can be arranged on the metal layer and then welded to the lead tab so that the lead tab can be welded to the metal sheet / metal layer stack or the metal sheet / metal layer / base film stack. When the base film, the metal layer, and / or the metal sheet melt during welding, the metal layer or the metal layer / metal sheet stack can be electrically connected to the lead tab. The metal sheet and / or the lead tab can be added to a part on the metal layer. The base film may have a thickness of, for example, about 1 μm to 50 μm, about 1.5 μm to about 50 μm, about 1.5 μm to about 40 μm, or about 1 μm to about 30 μm. Since the base film has a thickness in such a range, the weight of the electrode assembly can be reduced more effectively. The base film may have a melting point of, for example, about 100°C to about 300°C, about 100°C to about 250°C, or about 100°C to about 200°C. Since the base film has a melting point in such a range, the base film may melt and be easily bonded to the lead tab during welding of the lead tab. A surface treatment such as a corona treatment may be performed on the base film to improve adhesion between the base film and the metal layer. The base film may have a thickness of, for example, about 0.01 μm to about 3 μm, about 0.1 μm to about 3 μm, about 0.1 μm to about 2 μm, or about 0.1 μm to about 3 μm.Since the metal layer has a thickness within such a range, the stability of the electrode assembly can be ensured while maintaining conductivity. The metal sheet may have a thickness of, for example, about 2 μm to about 10 μm, about 2 μm to about 7 μm, or about 4 μm to about 6 μm. Since the metal sheet has a thickness within such a range, the connection between the metal layer and the lead tab can be more easily performed. Since the positive electrode current collector has such a structure, the weight of the positive electrode can be reduced, thereby improving the energy density of the positive electrode and the lithium battery.
[0093] (Diaphragm) Next, a separator to be inserted between the positive electrode and the negative electrode is prepared.
[0094] As the separator, any separator commonly used in lithium batteries can be used. For example, a separator having low resistance to the movement of ions in the electrolyte and having excellent electrolyte impregnation ability can be used. For example, the separator may include at least one selected from glass fiber, polyester, Teflon, PE, polypropylene (PP), PTFE, and a combination thereof, and may be in the form of a non-woven fabric or a woven fabric. For example, a windable separator including PE, PP, etc. can be used in a lithium ion battery, and a separator having excellent electrolyte impregnation ability can be used in a lithium ion polymer battery.
[0095] The separator is prepared by the following exemplary method, but one or more embodiments are not necessarily limited to such a method. The method can be adjusted according to the desired conditions.
[0096] First, a polymer resin, a filler and a solvent are mixed to prepare a separator composition. The separator composition can be directly applied to an electrode and dried to form a separator. Alternatively, the separator composition can be cast on a support, and then the separator film peeled off from the support is laminated on the electrode to form a separator.
[0097] The polymer resin used to prepare the separator is not particularly limited, and any material used in the bonding material of the electrode plate may be used. For example, the polymer resin may include vinylidene fluoride / hexafluoropropylene copolymer, PVDF, polyacrylonitrile, polymethyl methacrylate, or a mixture thereof.
[0098] (Electrolytes) Next, prepare the electrolyte.
[0099] The electrolyte may include, for example, a liquid electrolyte, a solid electrolyte, a gel electrolyte, or a combination thereof.
[0100] The electrolyte is, for example, an organic electrolyte. For example, a lithium salt is dissolved in an organic solvent to prepare an organic electrolyte.
[0101] Any material can be used as long as it is used as an organic solvent in the art. Examples of organic solvents can include propylene carbonate, ethylene carbonate (EC), fluoroethylene carbonate, butylene carbonate, dimethyl carbonate (DMC), diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof.
[0102] Any material can be used as long as it is used as a lithium salt in the art. Examples of lithium salts can include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (where 1 ≤ x ≤ 20 and 1 ≤ y ≤ 20), LiCl, LiI, or a mixture thereof. The concentration of the lithium salt can be, for example, in the range of about 0.1 M to about 5.0 M.
[0103] The solid electrolyte can be or include, for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer electrolyte, or a combination thereof.
[0104] The solid electrolyte can be, for example, an oxide-based solid electrolyte. The oxide-based solid electrolyte can include at least one selected from the following: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (where 0 < x < 2 and 0 ≤ y < 3), BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT) (where 0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y(PO4)3 (where 0 < x < 2 and 0 < y < 3), Li x Al y Ti z (PO4)3 (where 0 < x < 2, 0 < y < 1 and 0 < z < 3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), Li x La y TiO3 (where 0 < x < 2 and 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2 and Li 3+x La3M2O 12 (where M = Te, Nb or Zr, and x is an integer from 1 to 10). The solid electrolyte is prepared by sintering or the like. For example, the oxide - type solid electrolyte can be selected from Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O 12 (M - doped LLZO) (where M = Ga, W, Nb, Ta or Al, and x is an integer from 1 to 10) of garnet - type solid electrodes.
[0105] The sulfide - type solid electrolyte can include, for example, lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide or a combination thereof. The sulfide - type solid electrolyte particles can include Li2S, P2S5, SiS2, GeS2, B2S3 or a combination thereof. The sulfide - type solid electrolyte particles can include Li2S or P2S5. It is known that the sulfide - type solid electrolyte particles have a higher lithium - ion conductivity than other inorganic compounds. For example, the sulfide - type solid electrolyte can include Li2S and P2S5. When the sulfide solid electrolyte material constituting the sulfide - type solid electrolyte includes Li2S - P2S5, the mixing molar ratio of Li2S to P2S5 can be, for example, in the range of about 50:50 to about 90:10. In addition, it is possible to use by adding Li3PO4, halogens, halogen compounds, Li 2+2x Zn 1-x GeO4 (“LISICON”) (where 0 ≤ x < 1), Li 3+y PO 4-x N x (LIPON) (where 0 < x < 4 and 0 < y < 3), Li3.25 Ge 0.25 P 0.75 Inorganic solid electrolytes prepared from, for example, S4 (“thio-LISICON”), Li2O-Al2O3-TiO2-P2O5 (“LATP”), etc. are used as sulfide-based solid electrolytes. Non-limiting examples of sulfide-based solid electrolyte materials include Li2S-P2S5, Li2S-P2S5-LiX (where X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where 0 < m < 10, 0 < n < 10, and Z = Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, and Li2S-SiS2-Li p MO q(0 < p < 10, 0 < q < 10, and M = P, Si, Ge, B, Al, Ga, or In). In this regard, the sulfide-based solid electrolyte material can be prepared by treating the raw starting materials (e.g., Li2S or P2S5) of the sulfide-based solid electrolyte material via processes such as melt quenching, mechanical grinding, etc. Further, a calcination process can be performed after this treatment. The sulfide-based solid electrolyte can be in an amorphous state, a crystalline state, or a mixture state thereof. The polymer solid electrolyte can include, for example, a mixture of a lithium salt and a polymer or a polymer having an ion-conductive functional group. The polymer solid electrolyte can be, for example, a polymer electrolyte in a solid state at a temperature of about 25°C and a pressure of about 1 atm. The polymer solid electrolyte may not include, for example, a liquid. The polymer solid electrolyte can include, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), poly(vinylidene fluoride - hexafluoropropylene) (PVDF-HFP), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methyl methacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), poly(ethylenedioxythiophene) (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone sulfone) (SPAEKKS), sulfonated poly(aryl ether ketone) (SPAEK), poly[bis(benzimidazolo benzisoquinolinone)] (SPBIBI), poly(styrene sulfonate) (PSS), lithium 9,10-diphenylanthracene-2-sulfonate, DPASi + or a combination thereof, but one or more embodiments are not limited thereto. Any material used as a polymer electrolyte in the art can be used. As the lithium salt, any material available as a lithium salt in the art can be used. The lithium salt can include, for example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1SO2) (wherein, x and y are each 1 to 20), LiCl, LiI or a mixture thereof. The polymer included in the polymer solid electrolyte can be, for example, a compound including 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The polymer included in the polymer solid electrolyte can have, for example, a weight average molecular weight of 1,000 Daltons or more, 10,000 Daltons or more, 100,000 Daltons or more, or 1,000,000 Daltons or more.
[0106] The gel electrolyte may be or include, for example, a polymer gel electrolyte. The gel electrolyte may have a gel state without including, for example, a polymer.
[0107] The polymer gel electrolyte may include, for example, a liquid electrolyte and a polymer or may include an organic solvent and a polymer having an ion conductive functional group. The polymer gel electrolyte may be, for example, a polymer gel electrolyte that is in a gel state at a temperature of about 25° C. and a pressure of about 1 atm. The polymer gel electrolyte may have, for example, a gel state without including a liquid. The liquid electrolyte used in the polymer gel electrolyte may include, for example: a mixture of an ionic liquid, a lithium salt, and an organic solvent; a mixture of a lithium salt and an organic solvent; a mixture of an ionic liquid and an organic solvent; or a mixture of a lithium salt and an ionic liquid. The polymer used in the polymer gel electrolyte may be selected from the polymer used in the solid polymer electrolyte. The organic solvent may be selected from the organic solvent used in the liquid electrolyte. The lithium salt may be selected from the lithium salt used in the polymer solid electrolyte. The ionic liquid may have a melting point below room temperature, may include only ions, and may refer to a salt that is in a liquid state at room temperature or a molten salt at room temperature. The ionic liquid may include, for example, at least one selected from the group consisting of compounds comprising a and b: a) at least one cation selected from the group consisting of ammonium cations, pyrrolidinium cations, pyridinium cations, pyrimidinium cations, imidazolium cations, piperidinium cations, pyrazolium cations, oxazolium cations, pyridazinium cations, phosphonium cations, sulfonium cations, triazolium cations and mixtures thereof; and b) at least one cation selected from the group consisting of BF4 - PF6 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - , Cl - Br - ,I - 、BF4 - 、SO4- CF3SO3 - 、(FSO2)2N - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N - and (CF3SO2)2N - At least one anion in the electrolyte. For example, the polymer solid electrolyte can be immersed in a liquid electrolyte in a lithium battery to form a polymer gel electrolyte. The polymer gel electrolyte may also include inorganic particles. The polymer included in the polymer gel electrolyte may be, for example, a compound including 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The polymer included in the polymer gel electrolyte may have, for example, a weight average molecular weight of 500 Daltons or more, 1,000 Daltons or more, 10,000 Daltons or more, 100,000 Daltons or more, or 1,000,000 Daltons or more.
[0108] (Lithium battery) Reference Figure 5 According to one embodiment, a lithium battery 1 may include a positive electrode 3, the above-mentioned negative electrode 2, and a separator 4. The positive electrode 3, the negative electrode 2, and the separator 4 may be wound or folded to form a battery structure 7. The formed battery structure 7 may be housed in a battery case 5. An organic electrolyte may be injected into the battery case 5, and the battery case 5 may be sealed with a cap assembly 6 to complete the lithium battery 1. The battery case 5 may have a cylindrical shape, but one or more embodiments are not necessarily limited to such a shape. For example, the battery case 5 may have a prismatic shape, a film shape, etc.
[0109] Reference Figure 6 According to one embodiment, a lithium battery 1 may include a positive electrode 3, the above-mentioned negative electrode 2, and a separator 4. The separator 4 may be disposed between the positive electrode 3 and the negative electrode 2, and the positive electrode 3, the negative electrode 2, and the separator 4 may be wound or folded to form a battery structure 7. The formed battery structure 7 may be housed in a battery case 5. The lithium battery 1 may include an electrode tab 8 serving as an electrical path for guiding the current formed in the battery structure 7 to the outside. An organic electrolyte may be injected into the battery case 5, and the battery case 5 may be sealed to complete the lithium battery 1. The battery case 5 may have a prismatic shape, but one or more embodiments are not necessarily limited to such a shape. For example, the battery case 5 may have a cylindrical shape, a thin film shape, etc.
[0110] Reference Figure 7According to one embodiment, a lithium battery 1 may include a positive electrode 3, the above-mentioned negative electrode 2, and a separator 4. The separator 4 may be disposed between the positive electrode 3 and the negative electrode 2 to form a battery structure 7. The battery structure 7 may be stacked in a dual-cell structure and then housed in a battery case 5. The lithium battery 1 may include an electrode tab 8 serving as an electrical path for guiding the current formed in the battery structure 7 to the outside. An organic electrolyte may be injected into the battery case 5, and the battery case 5 may be sealed to complete the lithium battery 1. The battery case 5 may have a prismatic shape, but one or more embodiments are not necessarily limited to such a shape. For example, the battery case 5 may have a cylindrical shape, a thin film shape, etc.
[0111] Pouch type lithium battery corresponds to a battery in which the pouch is used as Figures 5 to 7 The case of a battery case in a lithium battery. A pouch-type lithium battery may include one or more battery structures. The separator may be disposed between the positive electrode and the negative electrode to form a battery structure. After the battery structure is stacked in a dual-cell structure, the battery structure may be immersed in an organic electrolyte, contained in a bag, and sealed to complete the pouch-type lithium battery. For example, although not shown in the accompanying drawings, the above-mentioned positive electrode, negative electrode, and separator may be simply stacked and contained in a bag in the form of an electrode assembly, or may be wound or folded into a core-shaped electrode assembly and then contained in a bag. Subsequently, the organic electrolyte may be injected into the bag, and the bag may be sealed to complete the lithium battery.
[0112] Lithium batteries may have excellent life characteristics and high rate characteristics, and thus may be used, for example, in electric vehicles (EVs). For example, lithium batteries may be used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs). In addition, lithium batteries may be used in fields that require the storage of large amounts of electricity. For example, lithium batteries may be used in electric bicycles, electric tools, and the like.
[0113] A plurality of lithium batteries can be stacked to form a battery module, and a plurality of battery modules can form a battery pack. The battery pack can be used for all devices that require high capacity and high output power. For example, the battery pack can be used for laptop computers, smart phones, electric vehicles, etc. The battery module may include, for example, a plurality of batteries and a frame for supporting the plurality of batteries. The battery pack may include, for example, a plurality of battery modules and a bus bar for connecting the plurality of battery modules. The battery module and / or the battery pack may also include a cooling device. The plurality of battery packs may be controlled by a battery management system. The battery management system may include a battery pack and a battery controller connected to the battery pack.
[0114] The above negative electrode can be applied to a lithium metal battery including a solid electrolyte. The lithium metal battery including the above negative electrode and the solid electrolyte will be described in more detail below.
[0115] (All-solid lithium metal battery) The lithium metal battery may be, for example, an all-solid lithium metal battery including a solid electrolyte. The all-solid lithium metal battery may include the above-mentioned negative electrode, and thus may have both improved capacity and excellent life characteristics.
[0116] For example, the all-solid lithium battery can be manufactured by the following exemplary method, but one or more embodiments are not necessarily limited to such a method. The method can be adjusted according to the required conditions.
[0117] Reference Figure 8 and Fig. 9 The all-solid lithium metal battery 1 may include a positive electrode 10, the above-mentioned negative electrode 20, and a solid electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20. The solid electrolyte layer 30 may include, for example, an inorganic solid electrolyte. The solid electrolyte layer 30 may include, for example, a sulfide-based solid electrolyte or an oxide-based solid electrolyte.
[0118] (Negative electrode) Prepare the negative electrode as described above.
[0119] (Positive electrode) Reference Figure 8 and Fig. 9 The positive electrode 10 may include a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on the positive electrode current collector 11. The positive electrode active material layer 12 may include a positive electrode active material. For the positive electrode active material, refer to the above-mentioned lithium battery section.
[0120] In addition to the positive electrode active material, the positive electrode active material layer 12 may further include a solid electrolyte. The solid electrolyte included in the positive electrode 10 may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30. For details of the solid electrolyte included in the positive electrode 10, refer to the part of the solid electrolyte layer 30.
[0121] The solid electrolyte used in the positive electrode active material layer 12 may have a D50 average particle size smaller than the D50 average particle size of the solid electrolyte used in the solid electrolyte layer 30. For example, the D50 average particle size of the solid electrolyte used in the positive electrode active material layer 12 may be 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less of the D50 average particle size of the solid electrolyte used in the solid electrolyte layer 30. The D50 average particle size of the solid electrolyte used in the positive electrode active material layer 12 may be in the range of, for example, about 0.1 μm to about 2 μm, about 0.2 μm to about 1.5 μm, or about 0.3 μm to about 1.0 μm.
[0122] Relative to the total weight of the positive electrode active material layer 12, the content of the solid electrolyte included in the positive electrode active material layer 12 may be in the range of about 1wt% to about 15wt%, about 5wt% to about 15wt%, or about 8.0wt% to about 12.0wt%. The positive electrode active material layer 12 may include a binder. The binder may include, for example, SBR, polytetrafluoroethylene, PVDF, PE, etc., but one or more embodiments are not necessarily limited thereto. Any material that can be used as a binder in the art may be used. Relative to the total weight of the positive electrode active material layer 12, the content of the binder included in the positive electrode active material layer 12 may be, for example, in the range of 0.1wt% to about 5wt%, about 0.5wt% to about 3wt%, or about 1.0wt% to about 2.0wt%.
[0123] The positive electrode active material layer 12 may include a conductive material. The conductive material may be, for example, a carbon-based conductive material or a metal-based conductive material. The conductive material may include, for example, graphite, CB, acetylene black, KB, carbon fiber, carbon nanotubes, metal powder, etc., but one or more embodiments are not necessarily limited thereto. Any material that can be used as a conductive material in the art may be used. Relative to the total weight of the positive electrode active material layer 12, the content of the conductive material included in the positive electrode active material layer 12 may be, for example, in the range of about 0.1wt% to about 10wt%, about 0.5wt% to about 5wt%, or about 1.0wt% to about 4.0wt%. In addition to the above-mentioned positive electrode active material, solid electrolyte, binder and conductive material, the positive electrode active material layer 12 may also include additives such as fillers, coating agents, dispersants and ion conductive adjuvants.
[0124] The positive electrode current collector 11 may be formed in the form of a plate, foil, or the like made of, for example, aluminum (Al), indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 may be omitted. The positive electrode current collector 11 may also include a carbon layer disposed on one surface or both surfaces of the metal substrate. Since the carbon layer is additionally disposed on the metal substrate, the metal of the metal substrate may be prevented from being corroded by the solid electrolyte included in the positive electrode, and the interface resistance between the positive electrode active material layer 12 and the positive electrode current collector 11 may be reduced. The carbon layer may have a thickness of, for example, about 1 μm to about 5 μm, about 1 μm to about 4 μm, or about 1 μm to about 3 μm. When the carbon layer is too thin, it may be difficult to completely block the contact between the metal substrate and the solid electrolyte. When the carbon layer is too thick, the energy density of the all-solid secondary battery may be reduced. The carbon layer may include amorphous carbon, crystalline carbon, and the like. The positive electrode current collector 11 including the metal substrate and optionally including the carbon layer may have a thickness of, for example, about 10 μm to about 50 μm, about 10 μm to about 40 μm, or about 10 μm to about 30 μm, but one or more embodiments are not necessarily limited thereto. The thickness of the positive electrode current collector 11 may be selected according to the desired characteristics of the all-solid lithium battery.
[0125] Although not shown in the drawings, in addition to the positive electrode current collector 11 and the positive electrode active material layer 12 disposed on the positive electrode current collector 11, the positive electrode 10 may further include an inactive member disposed on one side surface of the positive electrode active material layer 12. The area of the positive electrode active material layer 12 may be smaller than the area of the solid electrolyte layer 30 in contact with the positive electrode active material layer 12. The inactive member may be disposed to surround the side surface of the positive electrode active material layer 12 to correct the area error between the positive electrode active material layer 12 and the solid electrolyte layer 30. The inactive member is a member that does not include an electrochemically active substance (e.g., an electrode active substance). The electrode active substance is a material that inserts / deinserts lithium. The inactive member is a member made of a material used in the art other than the electrode active substance. The inactive member may surround the side surface of the positive electrode active material layer 12 and may be in contact with the solid electrolyte layer 30. Since the inactive member surrounds the side surface of the positive electrode active material layer 12 and contacts the solid electrolyte layer 30, cracks in the solid electrolyte layer 30 caused by the pressure difference during the pressing process in the solid electrolyte layer 30 not in contact with the positive electrode active material layer 12 can be effectively suppressed. The difference between the area of the positive electrode active material layer 12 and the area of the solid electrolyte layer 30 can be corrected due to the area of the inactive member, thereby effectively suppressing cracks in the solid electrolyte layer 30 caused by the pressure difference during the pressing process. The inactive member may be provided between the positive electrode current collector 11 and the solid electrolyte layer 30 facing each other. The inactive member may be used as a filler to fill the space between the positive electrode current collector 11 and the solid electrolyte layer 30 facing each other. The inactive member may include at least one selected from a lithium ion insulator and a lithium ion conductor. The inactive member may be an electronic insulator. That is, the inactive member may not be an electronic conductor. The inactive member may include an organic material, an inorganic material, or an organic-inorganic composite material. The organic material may be, for example, a polymer. The inorganic material may be, for example, a ceramic such as a metal oxide. The organic-inorganic composite material may be a composite of a polymer and a metal oxide. For example, the inactive member may include at least one selected from an insulating polymer, an ion conductive polymer, an insulating inorganic material, an oxide solid electrolyte, and a sulfide solid electrolyte. The inactive member may include, for example, an olefin polymer such as PP or PE. The inactive member may be, for example, a gasket. The thickness of the inactive member may be the same or similar to the thickness of the positive electrode active material layer 12.
[0126] (Solid electrolyte layer) Reference Figure 8 and Fig. 9 The solid electrolyte layer 30 may be disposed between the positive electrode 10 and the negative electrode 20 and may include a sulfide-based solid electrolyte.
[0127] The sulfide-based solid electrolyte may include, for example, at least one selected from the following: Li2S-P2S5, Li2S-P2S5-LiX (wherein X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are each positive numbers, and Z is one selected from Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are positive numbers, and M is one selected from P, Si, Ge, B, Al, Ga and In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS 6-x I x (wherein 0≤x≤2). The sulfide solid electrolyte can be prepared by treating a starting material such as Li2S or P2S5 by melt quenching or mechanical grinding. In addition, after such treatment, heat treatment can be performed. The solid electrolyte can be in an amorphous state, a crystalline state, or a mixture thereof. In addition, the solid electrolyte can be a material that includes at least sulfur (S), phosphorus (P) and lithium (Li) as constituent elements among the above-mentioned materials such as sulfide solid electrolytes. For example, the solid electrolyte can be a material including Li2S-P2S5. When a material including Li2S-P2S5 is used as a sulfide solid electrolyte material for forming a solid electrolyte, the mixed molar ratio of Li2S to P2S5 (e.g., Li2S:P2S5) can be in the range of about 50:50 to about 90:10.
[0128] The sulfide-based solid electrolyte may include, for example, an argyrodite-type solid electrolyte represented by Formula 1 below.
[0129] <Formula 1> Li + 12-n-x A n+ X 2- 6-x Y -x In Formula 1, A may be P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta, X may be S, Se or Te, Y may be Cl, Br, I, F, CN, OCN, SCN or N3, 1≤n≤5 and 0≤x≤2. The sulfide-based solid electrolyte may be, for example, a sulfide-based solid electrolyte selected from Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS 6-x I x (wherein 0≤x≤2). The sulfide-based solid electrolyte may be, for example, an argyrodite-type compound including at least one selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.
[0130] The argyrodite solid electrolyte may have a density of about 1.5 g / cc to about 2.0 g / cc. Since the argyrodite solid electrolyte has a density of 1.5 g / cc or more, it is possible to reduce the internal resistance of the all-solid secondary battery and effectively suppress Li from penetrating the solid electrolyte layer 30.
[0131] The elastic modulus (i.e., Young's modulus) of the sulfide solid electrolyte can be, for example, 35 GPa or less, 30 GPa or less, 27 GPa or less, 25 GPa or less, or 23 GPa or less. The elastic modulus (i.e., Young's modulus) of the sulfide solid electrolyte can be, for example, in the range of about 10 GPa to about 35 GPa, about 10 GPa to about 30 GPa, about 10 GPa to about 27 GPa, about 10 GPa to about 25 GPa, or about 10 GPa to about 23 GPa. Since the sulfide solid electrolyte has an elastic modulus within such a range, the temperature and / or pressure required for sintering is reduced, so the sintering of the solid electrolyte can be performed more easily.
[0132] The solid electrolyte used in the solid electrolyte layer 30 may have a D50 average particle diameter of, for example, about 1 μm to about 10 μm, about 1.5 μm to about 7 μm, or about 2 μm to about 5 μm.
[0133] The content of the sulfide-based solid electrolyte included in the solid electrolyte layer 30 may be, for example, in the range of about 97 wt % to about 100 wt %, about 98 wt % to about 99.9 wt %, or about 98.5 wt % to about 99.0 wt % relative to the total weight of the solid electrolyte layer 30 .
[0134] The solid electrolyte layer 30 may also include, for example, a binder. The binder included in the solid electrolyte layer 30 may include, for example, SBR, polytetrafluoroethylene, PVDF, PE, etc., but one or more embodiments are not limited thereto. Any material used as a binder in the art may be used. The binder of the solid electrolyte layer 30 may be the same as or different from the binder included in the positive electrode active material layer 12 and the negative electrode active material layer 23.
[0135] The content of the binder included in the solid electrolyte layer 30 may be, for example, in the range of about 0.1 wt % to about 3 wt %, about 0.5 wt % to about 2 wt %, or about 1.0 wt % to about 2.0 wt % relative to the total weight of the solid electrolyte layer 30 .
[0136] Reference Figure 8 and Fig. 9 , the all-solid lithium metal battery 1 may include a solid electrolyte layer 30, a positive electrode 10 disposed on one surface of the solid electrolyte layer 30, and a negative electrode 20 disposed on the other surface of the solid electrolyte layer 30. The positive electrode 10 may include a positive electrode active material layer 12 in contact with the solid electrolyte layer 30 and a positive electrode current collector 11 in contact with the positive electrode active material layer 12. The negative electrode 20 includes a protective layer 22, the protective layer 22 is in contact with the solid electrolyte layer 30 and the protective layer 22 is in contact with the negative electrode current collector 21. Alternatively, the negative electrode 20 may include a negative electrode active material layer 23 and a protective layer 22, the protective layer 22 is in contact with the solid electrolyte layer 30, and the negative electrode current collector 21 is in contact with the negative electrode active material layer 23. In the all-solid lithium metal battery 1, for example, the positive electrode active material layer 12 and the protective layer 22 may be disposed on both surfaces of the solid electrolyte layer 30, respectively, and the positive electrode current collector 11 and the negative electrode current collector 21 may be disposed on the positive electrode active material layer 12 and the protective layer 22, respectively. For example, the all-solid lithium metal battery 1a can be prepared by disposing the positive electrode active material layer 12 and the protective layer 22 / negative electrode active material layer 23 on both sides of the solid electrolyte layer 30 and disposing the positive electrode collector 11 and the negative electrode collector 21 on the positive electrode active material layer 12 and the negative electrode active material layer 23, respectively. Alternatively, the protective layer 22, the solid electrolyte layer 30, the positive electrode active material layer 12 and the positive electrode collector 11 can be sequentially stacked on the negative electrode collector 21 to complete the all-solid lithium metal battery 1. Alternatively, the all-solid lithium metal battery 1a can be prepared by sequentially stacking the negative electrode active material layer 23, the protective layer 22, the solid electrolyte layer 30, the positive electrode active material layer 12 and the positive electrode collector 11 on the negative electrode collector 21.
[0137] [Method for preparing negative electrode] According to another embodiment, a method for preparing a negative electrode may include: providing a negative electrode current collector; disposing a second protective layer on the negative electrode current collector; and disposing a first protective layer on the second protective layer, wherein the first protective layer includes porous nanostructured particles and the second protective layer includes polar inorganic particles. A lithium metal battery including a negative electrode prepared by such a method may have improved cycle characteristics.
[0138] First, a negative electrode current collector is provided. For the negative electrode current collector, refer to the above-mentioned negative electrode part. For example, a copper foil is provided as the negative electrode current collector.
[0139] Next, a second protective layer is provided on the negative electrode current collector. For example, polar inorganic particles, a second binder, and a solvent are mixed to prepare a second slurry, and then the second slurry is applied to the negative electrode current collector and dried to provide a second protective layer. The coating method is not particularly limited, and the coating can be performed using a scraper or the like. For the polar inorganic particles and the second binder, refer to the above-mentioned section on the negative electrode. The solvent may be an organic solvent. The solvent may include, for example, N,N-dimethylacetamide, N-methylpyrrolidone (NMP), etc., but one or more embodiments are not necessarily limited thereto. Any material used as a solvent in the art may be used.
[0140] Next, a first protective layer is provided on the second protective layer. For example, porous nanostructured particles, a first binder and a solvent are mixed to prepare a first slurry, and then the first slurry is applied to the second protective layer and dried to provide the first protective layer. The coating method is not particularly limited, and the coating can be performed using a scraper or the like. For the porous nanostructured particles and the first binder, refer to the above-mentioned section on the negative electrode. The solvent can be an organic solvent. The solvent can include, for example, N,N-dimethylacetamide, NMP, etc., but one or more embodiments are not necessarily limited thereto. Any material used as a solvent in the art can be used.
[0141] The porous nanostructured particles may include, for example, MOFs. MOFs may be obtained commercially or directly synthesized.
[0142] MOF can be synthesized by known methods. The method for synthesizing MOF may include, for example, a solution method, a hydrothermal method, a solid phase synthesis method (mechanical chemical method), a microwave method, an ultrasonic method, etc., but one or more embodiments are not limited thereto. For MOF, for example, a complex with a metal ion or a metal-containing secondary structural unit (SBU) is prepared as a metal source. A compound including an organic ligand having two or more coordination functional groups is prepared as an organic ligand source. The metal source and the organic ligand source can be introduced into a solvent, mixed, and then stirred to prepare MOF. In such a mixing and stirring process, MOF is prepared.
[0143] MOF may include one or more metal clusters and organic ligands connecting the metal clusters. The metal clusters may include, for example, one or more metal ions. The metal clusters may be composed of, for example, M a X b where a is 1 to 10 and b is chosen to balance the charge of the cluster. For example, X can be O 2- 、N 3- , S 2- or a combination thereof. M may be, for example, Li + , K + 、Na + , Cs + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ 、V 2+ 、V 3+ 、V 4+ 、V 5+ , Mn 2+ 、Re 2+ , Fe 2+ , Fe 3+ 、Ru 3+ 、Ru 2+ , Os 2+ 、Co 2+ , Rh 2+ , Ir 2+ 、Ni 2+ , Pd 2+ , Pt 2+ , Cu 2 + 、Zn 2+ 、Cd 2+ , Hg 2+ 、Si 2+ ,Ge 2+ Sn 2+ , Pb 2+ For example, the organic ligand having two or more coordination functional groups may be selected from the ligands represented by the following Formulae 1a to 1k.
[0144] Formula 1a Formula 1b Formula 1c Formula 1d Formula 1e Formula 1f Formula 1g Formula 1i Formula 1j Formula 1k In the above formula, X can be hydrogen, -NHR, -N(R)2, halogen, C 1-10 Alkyl, C 6-18 Aryl or C 6-18 Aralkyl, -NH2, alkenyl, alkynyl, -O(alkyl), -NH(aryl), cycloalkyl, cycloalkenyl, cycloalkynyl, -(CO)R, -(SO2)R, -(CO2)R, -SH, -S(alkyl), -SO3H, -SO 3- M + , -COOH, -COO - M + 、-PO3H 2- 、-PO3H - M + 、-PO3 2- M 2+ or-PO3 2- M 2+ , -NO2, -CO2H, silyl derivatives, borane derivatives, ferrocene and other metallocenes, M can be a metal atom, R can be C 1-10 alkyl.
[0145] The method of preparing a negative electrode may further include providing a negative electrode active material layer between the second protective layer and the negative electrode current collector. The negative electrode active material layer may include, for example, lithium metal and / or a lithium alloy.
[0146] There is no particular limitation on the method of arranging a negative electrode active material layer between the second protective layer and the negative electrode current collector. For example, a negative electrode active material layer may be arranged on the negative electrode current collector before the second protective layer is arranged on the negative electrode current collector. There is no particular limitation on the method of arranging a negative electrode active material layer on the negative electrode current collector. For example, a lithium metal layer may be arranged on a metal substrate by sputtering or the like. Alternatively, for example, a lithium foil may be arranged on a metal substrate and rolled to prepare a copper foil / lithium foil stack. Alternatively, a stack in which a lithium metal layer is stacked on a copper foil may be commercially available and used. Alternatively, a composition comprising a lithium powder and a binder may be applied to a metal substrate and dried to prepare a stack. For lithium powder and a binder, refer to the section of the negative electrode described above. Alternatively, after preparing a negative electrode comprising a negative electrode current collector and a protective layer, a negative electrode active material layer may be arranged between the negative electrode current collector and the protective layer by charging. The negative electrode active material layer may be, for example, a plated lithium layer.
[0147] The inventive concept will be described in more detail through the following examples and comparative examples. However, the examples are only for illustrative purposes, and the scope of the inventive concept is not limited by the examples.
[0148] (Preparation of Porous Nanostructured Particles) Preparation Example 1 10 mL (0.064 M) of Cu(NO3)22.5H2O (99.5%) (manufactured by Sigma-Aldrich Co., Ltd.) and 10 mL (0.062 M) of trimesic acid (99.5%, BTC) (manufactured by Sigma-Aldrich Co., Ltd.) were introduced into 10 mL of ethanol (99.95%, anhydrous ethanol) (manufactured by Sigma-Aldrich Co., Ltd.), mixed and stirred at room temperature for 20 minutes to prepare a solution. The obtained mixture was collected by centrifugation (at 40,000 rpm for 10 minutes), washed several times with ethanol, and dispersed by ultrasonic treatment (for 5 minutes). The obtained blue centrifugation product was collected and vacuum dried at a temperature of 70°C for 2 hours to prepare solid Cu-BTC (HKUST-1). Cu-BTC has a particle size of 5 μm to 10 μm. The size of the nanopores included in Cu-BTC is 0.8 nm. The nanopores are regularly and periodically arranged in Cu-BTC. Negative ions are disposed on the surface of the nanopore, so the surface of the nanopore is substantially negatively charged. That is, since the surface of the nanopore is substantially formed by negative ions, the surface of the nanopore is anionic. Cu-BTC is a MOF.
[0149] (Manufacturing of negative electrodes and lithium metal batteries) Example 1: Cu substrate / LiF second protective layer / MOF first protective layer negative electrode (70wt% MOF) (Manufacturing of negative electrode) The Cu-BTC particles prepared in Preparation Example 1 and PVDF powder (weight average molecular weight (Mw) measured by GPC: 534,000 Dalton) (manufactured by Sigma-Aldrich LLC) as a first binder were introduced into N,N-dimethylacetamide (99%, DMAc manufactured by Sigma-Aldrich LLC) at a weight ratio of 70:30 and stirred overnight at a temperature of 60° C. to prepare a first composition.
[0150] LiF powder (manufactured by Sigma-Aldrich Co., Ltd.) was pulverized at 760 rpm for 12 hours using a planetary ball mill (Pulverisette 5) to prepare LiF nanoparticles having a particle size of 10 nm to 15 nm.
[0151] LiF nanoparticles and PVDF powder (weight average molecular weight (Mw) measured by GPC: 534,000 Dalton) (manufactured by Sigma-Aldrich LLC) as a second binder were introduced into N,N-dimethylacetamide (99%, DMAc manufactured by Sigma-Aldrich LLC) at a weight ratio of 30:70 and stirred overnight at 60° C. to prepare a second composition.
[0152] The second composition was applied on a copper (Cu) current collector having a thickness of 20 μm using a doctor blade, and then the solvent was removed at a temperature of 65° C. for 6 hours to prepare a second protective layer.
[0153] The first composition was applied on the second protective layer using a doctor blade, and the solvent was removed at a temperature of 65° C. for 6 hours to prepare a first protective layer. A protective layer having a double-layer structure including a first protective layer and a second protective layer was prepared.
[0154] A negative electrode having a negative electrode current collector / second protective layer / first protective layer structure is prepared.
[0155] exist Fig.10 2 is a scanning electron microscope image of a cross section of the prepared negative electrode.
[0156] like Fig.10 As shown in , it is confirmed that a protective layer having a double-layer structure in which a second protective layer is provided on a copper current collector and a first protective layer is provided on the second protective layer is provided. Due to the Cu-BTC particles, protrusions and depressions are formed on the surface of the first protective layer.
[0157] The first protective layer had a thickness of 7.34 μm, the second protective layer had a thickness of 6.55 μm, and the protective layers had a total thickness of 13.89 μm.
[0158] (Manufacturing of button batteries) A lithium foil having a thickness of 20 μm was used as a counter electrode, a polypropylene separator (Celgard 3510) was placed between the counter electrode and the negative electrode, and an electrolyte was injected to manufacture a button battery.
[0159] As the electrolyte, a solution of 1.15 M LiPF6 dissolved in EC+ethyl methyl carbonate (EMC)+DMC (volume ratio of 2:4:4) was used.
[0160] Example 2: Negative electrode of Cu substrate / LiF second protective layer / MOF first protective layer (50wt% MOF) A negative electrode and a button cell were manufactured in the same manner as in Example 1, except that the content of Cu-BTC included in the first protective layer was changed to 50 wt %.
[0161] Example 3: Negative electrode of Cu substrate / LiF second protective layer / MOF first protective layer (10wt% LiF) A negative electrode and a button cell were manufactured in the same manner as in Example 1, except that the content of LiF included in the second protective layer was changed to 10 wt %.
[0162] Comparative Example 1: Bare Cu Negative Electrode A negative electrode and a button cell were manufactured in the same manner as in Example 1, except that a copper current collector was used as the negative electrode without any change.
[0163] Comparative Example 2: Cu substrate / LiF second protective layer negative electrode (first protective layer omitted) A negative electrode and a button cell were manufactured in the same manner as in Example 1, except that the operation of disposing the first protective layer was omitted.
[0164] Comparative Example 3: Negative electrode of Cu substrate / MOF first protective layer (second protective layer omitted) A negative electrode and a button cell were manufactured in the same manner as in Example 1, except that the operation of disposing the second protective layer was omitted.
[0165] Evaluation Example 1: Charge / Discharge Test The lithium batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 3 were charged at 0.1 mA / cm 2 The battery was then charged at a constant current of 0.1 mA / cm 2 The battery is discharged at a constant current until the voltage reaches 1.0V (vs. Li).
[0166] Such cycles were repeated under the same conditions up to the 500th cycle.
[0167] The lithium battery was left to rest for 10 minutes after each charge / discharge cycle. Fig.11 Some of the room temperature charge / discharge test results are shown in Table 1 below. The charge / discharge efficiency is defined by Equation 1 below.
[0168] The number of cycles at which the charge / discharge efficiency dropped to 80% or less is shown in Table 1 below.
[0169] <Equation 1> Charge / discharge efficiency [%] = [discharge capacity in the Nth cycle / charge capacity in the Nth cycle] × 100 [Table 1]
[0170] like Fig.11 As shown in Table 1, the lithium batteries of Examples 1 to 3 have improved lifespan characteristics compared to the lithium batteries of Comparative Examples 1 to 3.
[0171] It was determined that the improved lifespan characteristics of the lithium batteries of Examples 1 to 3 were due to the fact that due to the double-layer structure of the first protective layer including Cu-BTC and the second protective layer including LiF, side reactions caused by solvent decomposition on the surface of the negative electrode were suppressed and local current density imbalance was suppressed.
[0172] In the lithium batteries of Comparative Examples 1 to 3, it was determined that the protective layer could not effectively suppress a side reaction with the solvent and / or a local current density imbalance.
[0173] Although the embodiments have been described in detail with reference to the accompanying drawings, the inventive concept is not limited to the embodiments. It is obvious to those skilled in the art that various changes and modifications can be conceived within the scope of the technical ideas described in the claims, and these changes and modifications are understood to naturally belong to the technical scope of the inventive concept.
[0174] Description of reference numerals designating essential elements of the drawings 1. 1a: lithium battery; 2. 20: negative electrode 3, 10: positive electrode; 4: separator 5: Battery housing; 6: Cover assembly 7: Battery structure; 8: Electrode terminal block 11: Positive electrode current collector; 12: Positive electrode active material layer 21: negative electrode current collector; 22: protective layer 22a: first protective layer; 22b: second protective layer 23: Negative electrode active material layer; 30: Solid electrolyte layer.
[0175] Industrial Applicability According to one aspect, by adopting a negative electrode having a novel protective layer structure, a lithium metal battery having improved cycle characteristics can be provided.
Claims
1. A negative electrode for a lithium metal battery, the negative electrode comprising: negative electrode current collector; as well as A protective layer is disposed on the negative electrode current collector, The protective layer includes a first protective layer and a second protective layer disposed between the first protective layer and the negative electrode current collector. The first protective layer includes porous nanostructured particles, and The second protective layer includes polar inorganic particles.
2. The negative electrode according to claim 1, wherein The porous nanostructured particles include nanopores, and the nanopores have a size of 10 nm or less.
3. The negative electrode according to claim 2, wherein The nanopores are regularly or periodically arranged, and negative ions are disposed on surfaces of the nanopores.
4. The negative electrode according to claim 1, wherein The porous nanostructured particles include metal organic frameworks, polyhedral oligomeric silsesquioxanes, nanoporous silicon, nanoporous oxynitride, or combinations thereof.
5. The negative electrode according to claim 1, wherein The porous nanostructured particles have a size of 100 nm to 5 μm.
6. The negative electrode according to claim 1, wherein The content of the porous nanostructured particles is in the range of 50 wt % to 99 wt % relative to the total weight of the first protective layer.
7. The negative electrode according to claim 1, wherein The surface of the first protective layer includes protrusions and depressions, The protrusions are formed by the porous nanostructured particles, and the depressions are formed by pores between adjacent ones of the porous nanostructured particles.
8. The negative electrode according to claim 1, wherein The first protective layer also includes a first adhesive, The first adhesive comprises a fluorine-based adhesive, and The first protective layer includes 1 to 50 parts by weight of the first binder relative to 100 parts by weight of the porous nanostructured particles.
9. The negative electrode according to claim 1, wherein The polar inorganic particles have a dielectric constant of 5.0 or more and have crystallinity.
10. The negative electrode according to claim 1, wherein The polar inorganic particles are nanoparticles with a size less than 1 μm, The polar inorganic particles have a size of 10 nm to 200 nm, The size of the polar inorganic particles is smaller than the size of the porous nanostructured particles, and The size of the polar inorganic particles is 50% or less of the size of the porous nanostructured particles.
11. The negative electrode according to claim 1, wherein The polar inorganic particles include LiF; LiOH; Li2O; Li2CO3; Li3PO4; LiAlO2; Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2; HfO2; SrTiO3; SnO2; CeO2; Na2O; MgO; NiO; CaO; BaO; ZnO; ZrO2; Y2O3; Al2O3; TiO2; SiO2; SiC; Li 3+x La3M2O 12 , where M = Te, Nb or Zr, and 0 ≤ x ≤ 5; Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 , where 0 < x < 2 and 0 ≤ y < 3; BaTiO3; Pb(Zr p Ti 1-p )O3, where 0 ≤ p ≤ 1; Pb 1-x La x Zr 1-y Ti y O3, where 0 ≤ x < 1 and 0 ≤ y < 1; Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3; Li x Ti y (PO4)3, where 0 < x < 2 and 0 < y < 3; Li x Al y Ti z (PO4)3, where 0 < x < 2, 0 < y < 1 and 0 < z < 3; Li 1+x+y (Al p Ga 1-p ) x (Ti q Ge 1-q ) 2-x Si y P 3-y O 12 , where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ p ≤ 1 and 0 ≤ q ≤ 1; Li x La y TiO3, where 0 < x < 2 and 0 < y < 3; Li x Ge y P z S w , where 0 < x < 4, 0 < y < 1, 0 < z < 1 and 0 < w < 5; Li x N y , where 0 < x < 4 and 0 < y < 2; Li x Si y S z , where 0 < x < 3, 0 < y < 2, and 0 < z < 4; Li x P y S z , where 0 ≤ x < 3, 0 < y < 3, and 0 < z < 7; or a combination thereof.
12. The negative electrode according to claim 1, wherein The content of the polar inorganic particles is in the range of 1 wt % to 50 wt % of the total weight of the second protective layer.
13. The negative electrode according to claim 1, wherein The second protective layer further comprises a second adhesive, wherein the second adhesive comprises a fluorine-based adhesive, and The second protective layer includes 100 to 1,000 parts by weight of the second binder relative to 100 parts by weight of the polar inorganic particles.
14. The negative electrode according to claim 1, wherein The first protective layer has a thickness of 100 nm to 20 μm, the second protective layer has a thickness of 100 nm to 15 μm, and The protective layer has a total thickness of 200 nm to 25 μm.
15. The negative electrode according to claim 1, wherein The thickness of the second protective layer is smaller than the thickness of the first protective layer, and The thickness of the second protective layer is 95% or less of the thickness of the first protective layer.
16. The negative electrode according to claim 1, further comprising a negative electrode active material layer disposed between the negative electrode current collector and the protective layer, in, The negative electrode active material layer includes lithium metal or lithium alloy.
17. The negative electrode according to claim 16, wherein The negative electrode active material layer comprises lithium foil, lithium powder, plated lithium, carbon-based material or a combination thereof, and The negative electrode active material layer has a thickness of 0.1 μm to 80 μm.
18. A lithium metal battery, comprising: Positive electrode; The negative electrode according to any one of claims 1 to 17; as well as An electrolyte is disposed between the positive electrode and the negative electrode.
19. The lithium metal battery according to claim 18, wherein The electrolyte includes a liquid electrolyte, a solid electrolyte, a gel electrolyte or a combination thereof, The solid electrolyte includes an oxide solid electrolyte, a sulfide solid electrolyte, a polymer electrolyte or a combination thereof, and The gel electrolyte includes a polymer gel electrolyte.
20. The lithium metal battery according to claim 18, wherein The positive electrode includes a positive electrode current collector, and the negative electrode includes a negative electrode current collector, wherein at least one of the positive electrode current collector and the negative electrode current collector comprises a base film and a metal layer disposed on one surface or both surfaces of the base film, The base film includes a polymer including polyethylene terephthalate, polyethylene, polypropylene, polybutylene terephthalate, polyimide, or a combination thereof, and The metal layer includes indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, lithium or alloys thereof.
21. A method for manufacturing a negative electrode for a lithium metal battery, the method comprising the steps of: providing a negative electrode current collector; Disposing a second protective layer on the negative electrode current collector; as well as providing a first protective layer on the second protective layer, Wherein, the first protective layer comprises porous nanostructured particles, and The second protective layer includes polar inorganic particles. 22 . The method according to claim 21 , further comprising the step of providing a negative electrode active material layer between the second protection layer and the negative electrode current collector.